2023
DOI: 10.1038/s41598-023-37502-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus and Epstein–Barr virus co-infected young and middle-aged adults can have an aging-related T-cell phenotype

Abstract: Cytomegalovirus (CMV) is known to alter circulating effector memory or re-expressing CD45RA+ (TemRA) T-cell numbers, but whether Epstein–Barr virus (EBV) does the same or this is amplified during a CMV and EBV co-infection is unclear. Immune cell numbers in blood of children and young, middle-aged, and senior adults (n = 336) were determined with flow cytometry, and additional multivariate linear regression, intra-group correlation, and cluster analyses were performed. Compared to non-infected controls, CMV-se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Additionally, it has been reported that EBV-infected B cells trigger a G1 cellular arrest phase and exhibit augmented markers of OIS, such as H3K9me3 senescence-associated heterochromatic foci, p16, p21 and p53 in ( Nikitin et al., 2010 ; Nikitin et al., 2014 ; McFadden et al., 2016 ) ( Figure 2 ). Recently, it has been reported that co-infection with EBV and HCMV in young and middle-aged adults can alter T cell composition towards an aging-related T cell phenotype ( Hofstee et al., 2023 ).…”
Section: Interplay Between Systemic Infections and Immunosenescencementioning
confidence: 99%
“…Additionally, it has been reported that EBV-infected B cells trigger a G1 cellular arrest phase and exhibit augmented markers of OIS, such as H3K9me3 senescence-associated heterochromatic foci, p16, p21 and p53 in ( Nikitin et al., 2010 ; Nikitin et al., 2014 ; McFadden et al., 2016 ) ( Figure 2 ). Recently, it has been reported that co-infection with EBV and HCMV in young and middle-aged adults can alter T cell composition towards an aging-related T cell phenotype ( Hofstee et al., 2023 ).…”
Section: Interplay Between Systemic Infections and Immunosenescencementioning
confidence: 99%